Reform of Indonesian Criminal Law Reviewed From Law Number 1 of 2023 About the Criminal Code" - Dibi Vation Manik; Yasmirah Mandasari Saragih; Fauzan Fauzan; Eka Suwirza; Romy Rohadi Saragih (International Journal of Sociology and Law, 2025)
Law Number 1 of 2023 concerning the Criminal Code (KUHP) is an important milestone in criminal law reform in Indonesia. This study aims to analyze the innovations presented in the new Criminal Code and the challenges of its implementation. Therefore, based on the legal reform through the latest Criminal Code, it can be seen what the reforms in criminal law are according to Law Number : 1 of 2023 concerning the Criminal Code, why Law Number: 1 of 2023 concerning the Criminal Code needs to be reformed, and how the implementation will be in the future in the application of Law Number: 1 of 2023 concerning the Criminal Code. This study uses a juridical-normative method with a statutory and conceptual approach, this study found that the new Criminal Code introduces the concept of restorative justice , recognition of customary law, and protection of vulnerable groups as a step towards modernization. However, its implementation faces challenges, such as the readiness of law enforcement officers, harmonization of customary and national law, and the potential for misuse of articles that are considered controversial. Nevertheless, the new Criminal Code has the prospect of strengthening Indonesia's criminal law system if supported by strict supervision, training of law enforcement officers, and involvement of various stakeholders. This reform is expected to create a legal system that is fairer, more responsive, and more relevant to the needs of society.